Women, Peace, and Education: Gendered Dimensions of Multicultural Harmony in Singkawang - Ayu Gintari (Proceeding of the International Conference on Global Education and Learning, 2025)
This study analyzes the role of women in sustaining social harmony and strengthening multicultural education within the multiethnic society of Singkawang through a critical literature review approach. By integrating the Feminist Peace Theory and Multicultural Education Theory, this research examines both national and international scholarly works that explore women’s contributions to peacebuilding and multicultural education in Southeast Asia. The review reveals that women serve as cultural mediators, peace educators, and social innovators through interethnic and interfaith engagements such as cultural festivals, interreligious forums, and community-based initiatives. Despite notable progress in promoting multicultural education in Singkawang, gender perspectives remain insufficiently integrated into educational practices. Through a synthesis of the reviewed literature, this study proposes a conceptual framework of Gendered Multicultural Peace Education (GMPE), comprising three interrelated dimensions: women’s empowerment in educational and social leadership, empathy-based interethnic learning, and the integration of gender equality into curricula and school culture. The model underscores the strategic role of women as transformative agents and peace educators in multiethnic societies. The findings provide significant implications for the development of gender-sensitive and inclusive educational policies in Indonesia